Development of a permethylation-based detection method for oligo/polysialic acid structures via tandem MALDI-TOF mass spectrometry - Kai Suzuki; Di Wu; Ken Kitajima; Nao Yamakawa; Takayuki Omoto; Masaya Hane; Chihiro Sato (BBA Advances)
Oligo/polysialic acid (oligo/polySia) refers to a class of linear polymers composed of Sias, found extensively at the non-reducing ends of glycans across various organisms, from bacteria to vertebrates. Different types of oligo/polySia have been characterized, varying in Sia composition, α-ketosidic linkages to penultimate Sia residues, and degree of polymerization. Detection of oligo/polySia-capped glycans is typically achieved through western blotting or ELISA using specific antibodies or endo-N-acylneuraminidase. Additionally, a sensitive chemical approach involving the direct labeling of oligo/polySia with 1,2-diamino-4,5-methylenedioxybenzene, followed by separation and quantification via anion-exchange high-performance liquid chromatography, has been developed. However, detection through mass spectrometry (MS) has remained challenging due to the multiple negative charges and structural instability of these glycans. In this study, we applied a permethylation technique to convert carboxyl group of Sias into methyl esters, thereby neutralizing their negative charges, which allowed for improved MS analysis of sialylated glycans. We optimized both the permethylation and glycan purification processes. Consequently, we achieved the first successful detection of polySia structures using MALDI-TOF MS. There are more in-source decay ions in the MS profiling of permethylated α2,9-linked polySias compared to α2,8-linked polySias. Furthermore, we present the first examples of oligo/polySia sequencing by collision-induced dissociation on a TOF/TOF instrument, enabling us to differentiate between α2,8- and α2,9-linked polySias. We extended this approach to analyze oligo/polySia structures with O-linked glycans in polysialoglycoprotein from salmonid eggs. For the first time, the analysis of intact oligo/polySia structures with O-linked glycans were successfully detected using MALDI-TOF/TOF MS/MS with this optimized permethylation method.